The Marginalization of Teacher Education: Who We Are, How We Got Here, How We Fit in the Big Picture, and What We Might Do about It - Jones, Alan H. (Teacher education quarterly (Claremont, Calif.), 2010)
A watershed moment came when the Ryan Act was enacted in 1970, since that legislation strengthened the state's role in certification in ways that directly impacted teacher education practice, such as placing limits on the length of preparation programs and on the number of education units allowed prior to student teaching, and introducing the terminology of multiple and single subject credentials. [...] we are already doing it.